IMPOLITENESS STRATEGIES USED BY GOVERNOR CANDIDATES OF DKI JAKARTA IN GOVERNOR ELECTION DEBATE 2017 - Yohana Debora Siburian; Sri Minda Murni; Busmin Gurning (LINGUISTIK TERAPAN, 2019)
This study aimed at exploring the impoliteness strategies in governor election debate 2017. The objectives of the study were to describe, to explain how types of impoliteness strategies used and to expose the reasons. This research applied descriptive qualitative method. The data were the utterances of the governor candidates in two different debate sessions which were analyzed by using Culpeper Impoliteness Theory. The findings revealed that there were three out of five impoliteness strategies found in both debates, namely bald on record impoliteness, positive impoliteness and negative impoliteness. The governor candidates used the bald on record in three realizations, positive impoliteness in seven realizations and negative impoliteness in three realizations. There are some reasons of using the impoliteness strategies, namely to vent negative feelings, to mock others, to show disagreement, to show power, and to clarify something. However, the main reason to use the impoliteness strategies was to show power. Moreover, it is also revealed that both two different types of impoliteness strategies and two different realizations were used at the same moment.Keywords: election debate, governor candidates, impoliteness strategies